2012
DOI: 10.1093/erae/jbs025
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for environmental attributes of non-food agricultural products: a real choice experiment

Abstract: This paper investigates consumers' willingness to pay (WTP) a price premium for two environmental attributes of a non-food agricultural product. We study individual preferences for roses associated with an eco-label and a carbon footprint using an economic experiment combining discrete choice questions and real economic incentives involving real purchases of roses against cash. The data are analyzed with a mixed logit model and reveal significant premiums for both environmental attributes of the product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 35 publications
4
58
0
1
Order By: Relevance
“…Our results are consistent with Michaud et al (2013) who found lowering the carbon footprint of roses was valued more than applying a composite standard that comprised of energy efficiency, waste management, fertiliser use and social requirements. Conversely, Onozaka et al (2011) found that United States consumers valued reductions in the carbon footprint of tomatoes less than organic certification, and placed no value on carbon footprint reductions for apples.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with Michaud et al (2013) who found lowering the carbon footprint of roses was valued more than applying a composite standard that comprised of energy efficiency, waste management, fertiliser use and social requirements. Conversely, Onozaka et al (2011) found that United States consumers valued reductions in the carbon footprint of tomatoes less than organic certification, and placed no value on carbon footprint reductions for apples.…”
Section: Resultssupporting
confidence: 91%
“…The potential for carbon labelling of food products to change consumer behaviour has been recognised (Vanclay et al, 2011;Cohen & Vandenbergh, 2012) and the practice of carbon labelling is likely to grow in importance (Roos & Tjarnemo, 2011). While some attention has been focused on estimating monetary values of consumer preferences for changes in carbon emissions levels of food products (Caputo Nayga & Scarpa, 2013) including fruit (Aoki & Akai, 2013;Onozaka & McFadden, 2011) meat products (Koistinen et al, 2013) and non-food products including flowers (Michaud, Llerena, & Joly, 2013; and air travel (Mackerron, Egerton, Gaskell, Parpia, & Mourato, 2009) the literature is scarce relative to that for other credence attributes such as organics or food safety. This study is motivated by a need to improve understanding of the relative importance of multiple environmental sustainability attributes of primary sector fruit production including carbon emissions reductions.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that consumers are willing to pay a higher price for animal products obtained by means of production processes which enhance animal welfare has been shown by several studies (Lagerkvist and Hess 2010;Lusk and Norwood 2011b;Michaud et al 2013). However, what appear partly neglected in the literature are the determinants of consumer choices explaining the different sensitivities observed among individuals (and among different countries) toward animal welfare, both as a general concern and when it comes to food choices (Heerwagen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Conjoint Analysis (CA) has aroused great interest in the world of market research (Darby et al 2008;Michaud et al 2013). CA consists of a set of multivariate statistical methodologies that can detect those attributes of a product that are important in the evaluation process of the consumer, and thus determine the benefit associated with each characteristic of the product (partial utility) and, consequently, the global benefit (global utility).…”
mentioning
confidence: 99%